Loss of p27 phosphorylation at Ser10 accelerates early atherogenesis by promoting leukocyte recruitment via RhoA/ROCK. (July 2015) - Molina-Sánchez, P.; Chèvre, R.; Rius, C.; Fuster, J.J.; Andrés, V.
Abstract: Reduced phosphorylation of the tumor suppressor p27 Kip1 (p27) at serine 10 (Ser10) is a hallmark of advanced human and mouse atherosclerosis. Apolipoprotein E-null mice defective for this posttranslational modification (apoE −/− p27Ser10Ala) exhibited increased atherosclerosis burden at late disease states. Here, we investigated the regulation of p27 phosphorylation in Ser10 at the very initial stages of atherosclerosis and its impact on endothelial-leukocyte interaction and early plaque formation. Hypercholesterolemia in fat-fed apoE −/− mice is associated with a rapid downregulation of p27-phospho-Ser10 in primary endothelial cells (ECs) and in aorta prior to the development of macroscopically-visible lesions. We find that lack of p27 phosphorylation at Ser10 enhances the expression of adhesion molecules in aorta of apoE −/− mice and ECs, and augments endothelial-leukocyte interactions and leukocyte recruitment in vivo . These effects correlated with increased RhoA/Rho-associated coiled-coil containing protein kinase (ROCK) signaling in ECs, and inhibition of this pathway with fasudil reduced leukocyte-EC interactions to control levels in the microvasculature of p27Ser10Ala mice. Moreover, apoE −/− p27Ser10Ala mice displayed increased leukocyte recruitment and homing to atherosusceptible arteries and augmented early plaque development, which could be blunted with fasudil. In conclusion, our studies demonstrate a very rapid reduction in p27-phospho-Ser10 levels at the onset of atherogenesis, which contributes to early plaque build-up through RhoA/ROCK-induced integrin expression in ECs and enhanced leukocyte recruitment. Graphical abstract: Highlights: p27 is dephosphorylated at Ser10 in aorta of apoE-/- mice before ateroma development. Defective p27-phospho-Ser10 enhances VCAM-1 expression in aorta and endothelium. Defective p27-phopho-Ser10 augments leukocyte recruitment and early atherogenesis. RhoA/ROCK inhibition blunts proatherogenic effect of defective p27-phospho-Ser10.